Effect of feeding ammonia (urea) treated baled wheat straw with different levels of concentrate on nutrients utilization and growth of crossbred heifers - Pathak, Richa; Jaiswal, R S; Thakur, T C; Joshi, Y P; Pandey, Himanshu (The Indian Journal of Animal Sciences, 2005)
Crossbred heifers (16), 8-15 months old and 57-148 kg body weight, were divided into 4 comparable groups on the basis of weight and age. Treatments were untreated baled straw ad lib, and concentrate mixture to fulfil 100% CP and energy requirements (Tâ‚), ammonia (urea) treated baled wheat straw ad lib. and concentrate mixture to provide 100% CP and energy (Tâ‚‚), 75% CP and energy (Tâ‚ƒ), and 125% CP and energy requirements (Tâ‚„).The highest (3.72 kg/1OO kg body weight) and lowest (2.88 kg/100 kg body weight) DMI were recorded in urea treated baled wheat straw diet and concentrate mixture in Tâ‚„ and Tâ‚ƒ, respectively. Digestible dry matter intake values were 67.93,66.80,53.74 and 75.93 g/Kgwâ°â·âµ for Tâ‚ Tâ‚‚, Tâ‚ƒ and Tâ‚„ respectively. The straw DMI was 52.93,68.83,66.01 and 77.90 g/kgwâ°â·âµ for Tâ‚, Tâ‚‚, Tâ‚ƒ and Tâ‚„ respectively. There was no significant difference among treatments on total DMI, roughage DMI, CPI, DCP and digestible energy intake as percent body weight. Total energy intake (KCal/kgwâ°â·âµ) Tâ‚ was significantly higher (P